Mediating Role of Third-Party Logistics in The Relationship between Truck Operator Performance, Crane Rental Costs, and Information Integration Capability on Logistics Revenue at PT Nulin Sarana Jaya Balikpapan - Lisnawati Lisnawati; Maniah Maniah (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This study, entitled The Mediating Role of Third-Party Logistics in the Relationship between Truck Operator Performance, Crane Rental Costs, and Information Integration Capability on Logistics Revenue at PT Nulin Sarana Jaya Balikpapan, aims to analyze the direct and indirect relationships among the research variables. A quantitative research approach was employed using a sample of 117 customers selected through purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 3. The results indicate that Truck Operator Performance has a positive and significant effect on Third-Party Logistics (T = 4.222; p = 0.000) and Logistics Revenue (T = 4.102; p = 0.000). Crane Rental Costs positively and significantly affect Third-Party Logistics (T = 2.693; p = 0.007) and Logistics Revenue (T = 2.291; p = 0.020). Information Integration Capability positively and significantly influences Third-Party Logistics (T = 3.886; p = 0.000) and Logistics Revenue (T = 3.073; p = 0.004). Furthermore, Third-Party Logistics has a positive and significant effect on Logistics Revenue (T = 3.500; p = 0.000). The mediation analysis confirms that Third-Party Logistics significantly mediates the effects of Truck Operator Performance (T = 2.463; p = 0.014), Crane Rental Costs (T = 2.310; p = 0.021), and Information Integration Capability (T = 2.656; p = 0.008) on Logistics Revenue. These findings indicate that improving operational performance, optimizing crane rental costs, and strengthening information integration capability, supported by effective Third-Party Logistics management, can enhance the company's logistics revenue.